Cognitive function and ophthalmological diseases: the Beijing Eye Study - Jonas, Jost B. (Scientific reports, 2018)
To examine associations between cognitive function and ophthalmological parameters, the population-based Beijing Eye Study examined ophthalmologically and physically 3127 individuals (mean age: 64.2 ± 9.8 years). Using the mini-mental state examination, cognitive function was assessed as cognitive function score (CFS). Mean CFS was 26.3 ± 3.7 (median: 27; range: 2-30). Prevalence of mild (CFS: 23-19), moderate (CFS: 18-10) and severe cognitive dysfunction was 9.6% (95% confidence interval (CI): 8.5, 10.6), 3.2% (95% CI: 2.6, 3.9) and 0.6% (95% CI: 0.4,0.9), respectively. In multivariate analysis, better cognition (i.e., higher CFS) was significantly associated with better best corrected visual acuity (r2 = 0.38), smaller amount of undercorrected visual acuity, lower prevalence of primary angle-closure glaucoma, and thicker subfoveal choroidal thickness. Prevalence of age-related macular degeneration, open-angle glaucoma, diabetic retinopathy, any type of cataract, retinal vein occlusions or pseudoexfoliation was not significantly correlated with CFS. Though the causal relationship is unclear, the associations of lower cognitive function with undercorrected visual acuity suggest the need for earlier and more regular refraction testing in the elderly so that providing adequate glasses to the elderly can be provided and vision-associated cognitive decline can be reduced. Associations of cognitive function with primary angle-closure glaucoma and leptochoroid should be further explored.